Análise in silico da evolução de heveínas no reino vegetal - Veloso, Ludmila Marques dos Santos (2022)
Plants evolution suggests that Green Algae are the direct precursors of land plants, followed by Bryophytes and Pteridophytes. Throughout the evolutionary process, plants have become a source of biologically active molecules with diverse properties. Among these molecules we find several antimicrobial peptides (AMPs) families and among these, we can highlight hevein family, which are rich in cysteines, glycines and have the ability to bind chitin, making them a great potential biotechnological tool. This job verified hevein presence in Plantae kingdom species using bioinformatics tools. A literature search was performed for standard hevein sequences, followed by its sequences download. Sequences were submitted to the TBLASTN algorithm in the “1K Plants” database against the Green Algae, BBryophytes, PPteridophytes and CConifers transcriptomes. Conserved domains (PFAM IPRO001002 and PFAM IPRO001153) presence were verified using the INTERPROSCAN tool, followed by global alignment using MUSCLE tool. After confirming hevein presence, phylogenetic analysis and three-dimensional structures prediction were performed. It was possible to identify 5 hevein sequences, all of which have heveins basic physicochemical properties and three-dimensional structures and all belong to the 8C-Hev heveins class. The results suggest that the hevein found in higher plants today appeared in the Pteridophyte group after several mutation events, such as cleavage and translocation, from the Green Algae and bryophyte groups, which resulted in the hevein peptide. Therefore, we can conclude that heveis arose in PPteridophytes and the sequences identified belong to the 8C-Hev hevein class, the other hevein classes (6C-Hev and 10C-Hev) must have arisen in the Angiosperms group.